Análise numérica de nanofluidos escoando em um trocador de calor em túnel de vento - Nascimento, Erick Oliveira do (2024)
In the last decade there has been an intensification of studies on the thermal performance of heat exchangers, due to passive techniques, such as the use of fins and microchannels, having reached a technical limit, in addition to the low thermal conductivity of conventional refrigerant fluids, such as water, ethylene glycol (EG) and the EG-water mixture. In automobiles, low heat exchange triggers an increase in the weight of the radiators and drag, generated by the increase in surface area. Several researchers have dispersed nanometric-sized solid particles in base fluids, with the aim of increasing the thermal conductivity of these fluids and consequently increasing heat transfer in automotive radiators. However, experimental tests of automotive radiators present a high cost in purchasing materials and equipment, compared to computer simulations. This approach presents even greater advantages when using nanofluids as a working fluid, due to the difficulty of stabilization and the cost of purchasing nanoparticles, which are the main barriers to the experimental study of nanofluids. Therefore, this work aims to evaluate the thermohydraulic performance of graphene/EG-water nanofluids (50:50) in an automotive radiator in a wind tunnel using the finite volume method that is implemented in the Ansys Fluent software. Unlike other computer simulations of automotive radiators, this work considers the effects of heat conduction on the walls of the tube and fins, the variation in the properties of the coolant as a function of local temperature and the thermal boundary condition is not constant throughout along the heat exchanger. The results obtained computationally show satisfactory agreement with the experimental results for the base fluid. Numerically, gains of up to 12.13% in the heat transfer rate were observed for the nanofluid with a concentration of 0.10 vol.%, while experimentally the gain is only 3.3% in relation to the base fluid. For a concentration of 0.5 vol.%, an increase in heat transfer of up to 47.3% was identified. The thermohydraulic performance coefficient of the nanofluids was also evaluated, in which it was observed that all analyzed samples were superior to the base fluid, indicating promising results for applications in automotive radiators. Furthermore, a new correlation for the convective heat transfer process for graphene nanofluid was proposed.